Competitive Business Model for Organizing Regional Energy Supply in the Formation of the Unified Energy Market of the Eurasian Economic Union - Evgeny LISIN; Oksana KONOVALOVA; Valery LOZENKO (Communications of International Proceedings, 2020)
The paper examines the directions of development of power systems of the Eurasian Economic Union member countries when creating a unified electric power market. This problem is due to the fact that the key technology for energy production, which forms the basis of the energy systems of the post-Soviet countries, is the joint generation of electric and thermal energy at thermal power plants. At the same time, this type of combined production is ineffective in market conditions, and the creation of a unified energy market can significantly affect the economic efficiency of regional energy supply systems. In this regard, a unified competitive business model for organizing energy supply to regional consumers and a method for determining the marginal tariff based on market principles are proposed.
Keywords: Eurasian Economic Union; unified electric power market; combined power plants; energy supply systems; district heating; business models; performance evaluation.